The everlasting meal cookbook : leftovers A-Z - Adler, Tamar (Scribner, 2023)
"The award-winning, bestselling author of An Everlasting Meal serves up an inspiring, money-saving, environmentally responsible, A-to-Z collection of simple recipes that utilize all kinds of leftovers--perfect for solo meals or for feeding the whole family"--